HUBUNGAN PENGETAHUAN KANKER PAYUDARA DENGAN PERILAKU SADARI PADA REMAJA PUTRI DI SMA NEGERI 1 MANADO - Nadia Lady Carolina Malingkas; Sefti S. J. Rompas; Kristamuliana Kristamuliana (JURNAL KEPERAWATAN, 2022)
AbstractBackground: Breast cancer is one of the leading causes of death in females in Indonesia. One of the reasons for the increase in mortality due to breast cancer is that it is detected at an advanced stage. BSE is a technique to detect breast cancer at an earlier stage. Aim: The purpose of this research was to find out the relationship between knowledge of breast cancer and BSE behavior in teenage girls at SMA Negeri 1 Manado. Methods: The research method uses the quantitative method, comparative design with a cross-sectional approach. The research population is teenage girls in SMA Negeri 1 Manado with a total sample of 143 samples selected using the Simple Random Sampling technique. Data collection was conducted by utilizing a questionnaire and data analysis using Chi Square. Results: The results showed that good knowledge of breast cancer is at 53.1%, moderate at 45.5%, bad at 1.4%, and good BSE behavior is at 2.1%, moderate at 54.5%, bad at 43.4%. Conclusions: The conclusion of the research is that there is no relationship between knowledge of breast cancer and BSE behavior in teenage girls at SMA Negeri 1 Manado. It is recommended that the nursing service is expected to work together with the school to conduct counseling regarding BSE.